Association of Obesity and Anemia with the Dietary Pattern among the Nursing Students - Kaur, Sukhwinder; Dutta, Monika; Shaktan, Mumtesh; Sharma, Mridula; Sandhu, Monika; Anand, Mridu; Devi, Monika; Jamwal, Monika; Handa, Neha (International Journal of Nursing Research, 2023)
Aim: The aim of the study was to assess the association of obesity and anemia with the dietary pattern among the nursing students. Methodology: A descriptive study was conducted on 87 students of BSc Nursing final year of National Institute of Nursing Education, PGIMER, Chandigarh. Total enumeration sampling technique was used. An interview schedule consisting of socio-demographic profile, dietary pattern questionnaire, food frequency questionnaire, and 2-day recall was used for collecting data. In addition, BMI and hemoglobin levels were measured. Result: Among study subjects, nine (10.3%) were obese/overweight, 18 (20.6%) were anemic, and 63 (72.5%) had normal hemoglobin level and BMI. Out of nine obese/overweight subjects, four (44.4%) belonged to high socio-economic class, and six (66.7%) were non vegetarian. Habit of skipping meals was seen both in obese group six (66.7%) and in anemic group 11 (61.1%). The frequency of skipping meals among obese/overweight and anemic subjects was 2–3 meals. Daily consumption of snacks and fast food was also high both in obese/overweight 4 (44.4%) and anemic group 10(55.6%). Only three (33.3%) of obese/overweight group subjects and three (16.6%) of anemic subjects were consuming fruits daily. Calorie intake was high in eight (88.9%) of obesity/overweight group. Conclusion: Only the relation of BMI with the calorie intake was seen. People with greater BMI show calorie intake more than the recommended. The association was not assessed due to insufficient sample size. However, only percentages were calculated. Seventy-four (85.1%) subjects were hostellers and 63(72.5%) were still found to have normal BMI and hemoglobin values, thus concluding that they were consuming appropriate diet from the mess.b